1219Translating epidemiological findings to end rheumatic heart disease in Australia: the ERASE project. (2nd September 2021) - Katzenellenbogen, Assoc Judith; Stacey, Ingrid; Wade, Vicki; Haynes, Emma; Bessarab, Dawn
Abstract: Focus of Presentation: Rheumatic fever (RF) and rheumatic heart disease (RHD) are endemic among Indigenous Australians. End RHD in Australia: Study of Epidemiology (ERASE) aimed to characterize contemporary RF/RHD epidemiology. Using multi-jurisdictional linked data from several administrative sources, we undertook sub-studies covering diverse epidemiological questions, requiring substantial methods development. Mixed methods further identified barriers/facilitators to inform system redesign. Our multi-disciplinary collaboration supported diverse initiatives to contribute to policy at government, service and community/stakeholder levels. We show how findings from ERASE were applied/translated to address the impact of RF/RHD in Australia. Findings: Academic: >15 papers and commentaries/editorials provided the backbone to translational outputs and methods sharing. PhD students have ongoing projects using ERASE datasets. Advocacy: ERASE epidemiological and economic information supported the Endgame Strategy (roadmap for eliminating RHD in Australia by 2031) presented to government. Health professionals: ERASE data contributed to Australian RF/RHD guidelines. Slides of results/interpretation are publically-available on the RHDAustralia website. Student lectures integrate biomedical and culturally-informed perspectives. Indigenous stakeholder engagement: involves (1)presentations to peak Indigenous-controlled organisations (2)co-designed resources (booklets/slides) for capacity-building of RHDAustralia's national Champions4Change network (3)research workshops to promote two-way learning and health literacy/numeracy. Challenges remain regarding strengths-based approaches when reporting high disparities. Conclusions/Implications: Strong translational commitment and national multi-disciplinary networks of Indigenous and non-Indigenous collaborators ensured ERASE generated multiple outputs that continue to inform training, practice, policy and community health literacy. Key messages: Build translation and broad collaboration into study from the start.